Mental health in hospital emergency departments: cross-sectional analysis of attendances in England 2013/2014. Issue 12 (5th November 2020) - Baracaia, Simona; McNulty, David; Baldwin, Simon; Mytton, Jemma; Evison, Felicity; Raine, Rosalind; Giacco, Domenico; Hutchings, Andrew; Barratt, Helen
Abstract : Objective: To describe the population of patients who attend emergency departments (ED) in England for mental health reasons. Methods: Cross-sectional observational study of 6 262 602 ED attendances at NHS (National Health Service) hospitals in England between 1 April 2013 and 31 March 2014. We assessed the proportion of attendances due to psychiatric conditions. We compared patient sociodemographic and attendance characteristics for mental health and non-mental health attendances using logistic regression. Results: 4.2% of ED attendances were attributable to mental health conditions (median 3.2%, IQR 2.6% to 4.1%). Those attending for mental health reasons were typically younger (76.3% were aged less than 50 years), of White British ethnicity (73.2% White British), and resident in more deprived areas (59.9% from the two most deprived Index of Multiple Deprivation quintiles (4 and 5)). Mental health attendances were more likely to occur 'out of hours' (68.0%) and at the weekend (31.3%). Almost two-thirds were brought in by ambulance. A third required admission, but around a half were discharged home. Conclusions: This is the first national study of mental health attendances at EDs in England. We provide information for those planning and providing care, to ensure that clinical resources meet the needs of this patient group, who comprise 4.2% of attendances. In particular, we highlight the need to strengthen the availability of hospital and community care 'out of hours.'